DCD donor hemodynamics as predictor of outcome after kidney transplantation. Issue 8 (13th March 2018) - Peters‐Sengers, H.; Houtzager, J. H. E.; Heemskerk, M. B. A.; Idu, M. M.; Minnee, R. C.; Klaasen, R. W.; Joor, S. E.; Hagenaars, J. A. M.; Rebers, P. M.; van der Heide, J. J. Homan; Roodnat, J. I.; Bemelman, F. J.
Abstract : Insufficient hemodynamics during agonal phase—ie, the period between withdrawal of life‐sustaining treatment and circulatory arrest—in Maastricht category III circulatory‐death donors (DCD) potentially exacerbate ischemia/reperfusion injury. We included 409 Dutch adult recipients of DCD donor kidneys transplanted between 2006 and 2014. Peripheral oxygen saturation (SpO2‐with pulse oximetry at the fingertip) and systolic blood pressure (SBP‐with arterial catheter) were measured during agonal phase, and were dichotomized into minutes of SpO2 > 60% or SpO2 < 60%, and minutes of SBP > 80 mmHg or SBP < 80 mmHg. Outcome measures wereand primary non‐function (PNF), delayed graft function (DGF), and three‐year graft survival. Primary non‐function (PNF) rate was 6.6%, delayed graft function (DGF) rate was 67%, and graft survival at three years was 76%. Longer periods of agonal phase (median 16 min [IQR 11‐23]) contributed significantly to an increased risk of DGF ( P  = .012), but not to PNF ( P  = .071) and graft failure ( P  = .528). Multiple logistic regression analysis showed that an increase from 7 to 20 minutes in period of SBP < 80 mmHg was associated with 2.19 times the odds (95% CI 1.08‐4.46, P  = .030) for DGF. In conclusion, duration of agonal phase is associated with early transplant outcome. SBP < 80 mmHg during agonal phase shows a better discrimination for transplant outcome than SpO2 < 60% does. Abstract : This investigation of the predictive ability of hemodynamics during the agonal phase of circulatory death donors shows that systolic blood pressure discriminates short‐term transplant outcomes better than peripheral oxygenation does.